Knock three times - Cowell, Cressida (New York : Little, Brown and Company, 2019)
Xar and Wish are heroes with a huge task ahead--confronting the Nuckalavee is not for the faint hearted. But with Magic and Iron together, they might just have a chance of saving their beloved homes from those who seek to destroy everything they hold dear.
6.6
3-6
X
Keywords: Wizards -- Juvenile fiction; Witches -- Juvenile fiction; Magic -- Juvenile fiction; Wizards -- Fiction; Witches -- Fiction; Magic -- Fiction; Action and adventure fiction